THE ROLE OF MUSEUMS AS A CULTURAL HERITAGE ATTRACTION: KOTA KUALA KEDAH MUSEUM - Hamimi Omar; Nor Hanim Abdul Razak; Shamsul Bahrain Rawi; Asmahany Ramely, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Museums have historically been seen as cultural institutions whose prime functions are education and learning. However, as society has changed, more museums are aware of their potential to add value to their community economically by attracting visitors to the destination. As the demand for tourism increases, museums have become key partners in the cultural heritage tourism industry of a destination. Consequently, greater emphasis is now being placed on their leisure function. In parallel with the development of museums as visitor attraction, museums need to be the place where visitors can visit, see and experience the important aspects of the community and area within the destination. In this sense, the process of exhibiting, communicating and explaining to visitors the significance of the place or resources they are visiting is important in ensuring visitor satisfaction. In this paper, the role of Kota Kuala Kedah Museum as a cultural heritage tourism attraction in Kedah is explored. Findings revealed that the museum has great potential to attract visitors. The museum, furthermore, is able to connect the visitors with the historical values of the fort to the community in Kuala Kedah specifically, and Kedah generally. As a conclusion, this paper concludes that the management of Kota Kuala Kedah Museum should be ready to meet the challenge of practicing a more visitor friendly approach while continuing to meet their heritage preservation and education mandates.